Diagnostic accuracy of cancer antigen 125 for endometriosis: a systematic review and meta‐analysis. (12th May 2016) - Hirsch, M; Duffy, JMN; Davis, CJ; Nieves Plana, M; Khan, KS; ,
Abstract : Background: The development of a non‐invasive and accurate diagnostic biomarker for endometriosis is urgently needed. Objective: Evaluate the diagnostic accuracy of serum cancer antigen 125 (CA 125) for endometriosis. Search strategy: We searched EMBASE, MEDLINE, and Web of Science from inception to January 2016. Selection criteria: Diagnostic accuracy studies of serum CA 125 (index test) for histologically confirmed endometriosis (reference standard) were included. Data collection and analysis: Two authors independently selected trials, extracted study characteristics and data. Methodological quality was assessed using Quality Assessment of Comparative Diagnostic Accuracy Studies (QUADAS‐2) checklist. Main results: Twenty‐two studies (16 cohort, six case‐control), 3626 participants, were identified. Bivariate hierarchical models were used to pool accuracy data of 14 studies (2920 participants) using CA 125 ≥ 30 units/ml. Pooled specificity was 93% (95% CI 89–95%) and sensitivity 52% (95% CI 38–66%). CA 125 was significantly more sensitive for the diagnosis of moderate or severe endometriosis compared with minimal disease (63%, 95% CI 47–77% versus 24%, 95%CI 19–32%, P‐ value = 0.001). Conclusions: CA 125 performs well as a rule‐in test facilitating expedited diagnosis and ensuring investigation and treatment can be confidently tailored for the management of endometriosis. Unfortunately, a negative test, CA 125 < 30 units/ml, is unable to rule out endometriosis. Tweetable abstract: Blood test CA 125: a rule‐in test for the diagnosis of women presenting with symptoms of endometriosis Tweetable abstract: Blood test CA 125: a rule‐in test for the #diagnosis of women presenting with symptoms of #endometriosis. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14055